C-type natriuretic peptide co-ordinates cardiac structure and function - Chu, SM; Moyes, AJ; Aubdool, AA; Hobbs, AJ (Oxford University Press, 2019)
Aims: C-type natriuretic peptide (CNP) is an essential endothelium-derived signalling species that governs vascular homoeostasis; CNP is also expressed in the heart but an intrinsic role for the peptide in cardiac function is not established. Herein, we employ unique transgenic strains with cell-specific deletion of CNP to define a central (patho)physiological capacity of CNP in maintaining heart morphology and contractility. Methods and results: Cardiac structure and function were explored in wild type (WT), cardiomyocyte (cmCNP−/−), endothelium (ecCNP−/−), and fibroblast (fbCNP−/−)—specific CNP knockout mice, and global natriuretic peptide receptor (NPR)-B−/−, and NPR-C−/− animals at baseline and in experimental models of myocardial infarction and heart failure (HF). Endothelium-specific deletion of CNP resulted in impaired coronary responsiveness to endothelium-dependent- and flow-mediated-dilatation; changes mirrored in NPR-C−/− mice. Ex vivo, global ischaemia resulted in larger infarcts and diminished functional recovery in cmCNP−/− and NPR-C−/−, but not ecCNP−/−, vs. WT. The cardiac phenotype of cmCNP−/−, fbCNP−/−, and NPR-C−/− (but not ecCNP−/− or NPR-B−/−) mice was more severe in pressure overload- and sympathetic hyperactivation-induced HF compared with WT; these adverse effects were rescued by pharmacological CNP administration in WT, but not NPR-C−/−, mice. At a molecular level, CNP/NPR-C signalling is impaired in human HF but attenuates activation of well-validated pro-hypertrophic and pro-fibrotic pathways. Conclusion: C-type natriuretic peptide of cardiomyocyte, endothelial and fibroblast origins co-ordinates and preserves cardiac structure, function, and coronary vasoreactivity via activation of NPR-C. Targeting NPR-C may prove an innovative approach to treating HF and ischaemic cardiovascular disorders.